In vivo and in vitro hepatic phosphorus-31 magnetic resonance spectroscopy and electron microscopy in chronic ductopenic rejection of human liver allografts. Issue 5 (1st May 1998) - Taylor-Robinson, S D; Sargentoni, J; Bell, J D; Thomas, E L; Marcus, C D; Changani, K K; Saeed, N; Hodgson, H J F; Davidson, B R; Burroughs, A K; Rolles, K; Foster, C S; et al.
Abstract : Background —In vivo hepatic phosphorus-31 magnetic resonance spectroscopy (MRS) provides non-invasive information about phospholipid metabolism. Aims —To delineate MRS abnormalities in patients with chronic ductopenic rejection (CDR) and to characterise spectral changes by in vitro MRS and electron microscopy. Patients and methods —Sixteen liver transplant recipients (four with CDR; 12 with good graft function) and 29 controls (23 healthy volunteers; six patients with biliary duct strictures) were studied with in vivo 31 P MRS. Peak area ratios of phosphomonoesters (PME) and phosphodiesters (PDE), relative to nucleotide triphosphates (NTP) were measured. In vitro MRS and electron microscopy were performed on biopsy specimens from five patients with CDR, freeze clamped at retransplantation. Phosphoethanolamine (PE), phosphocholine (PC), glycerophosphorylethanolamine (GPE), and glycerophosphorylcholine (GPC) concentrations were measured. Results —The 12 patients with good graft function displayed no spectral abnormalities in vivo; the four patients with CDR showed significantly elevated PME:NTP (p<0.01) and PDE:NTP ratios (p<0.005). Patients with biliary strictures had significant differences in PME:NTP (p<0.01) from patients with CDR, but not in mean PDE:NTP. In vitro spectra from CDR patients showed elevated PE and PC, mirroring the in vivo changes in PME, but reduced GPE and GPC concentrations were observed, at variance with the in vivo PDE findings. On electron microscopy, there was no proliferation in hepatocyte endoplasmic reticulum. Conclusions —The increase in PME:NTP reflects altered phospholipid metabolism in patients with CDR, while the increase in PDE:NTP may represent a significant contribution from bile phospholipid.